Daoist political philosophy and Its Value for Contemporary Political Leadership - Nguyen Thi Thanh, Dung (Kalágatos, 2025)
In the context of globalization and the proliferation of socio-political crises, there is a growing demand for models of leadership that emphasize flexibility, humility, and adaptability. Eastern political philosophies have left profound legacies; however, most studies have focused on Confucianism and Legalism, while Daoism has often been regarded more as a mystical worldview than as a viable political theory. This article addresses this gap by examining Daoist political thought, particularly the concepts of Dao ( 道), De (德), and the principle of wu wei (無為), to analyze their significance for contemporary political leadership.